2022
DOI: 10.3390/bios12090756
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive and Semi-Quantitative Vertical Flow Assay for the Rapid Detection of Interleukin-6 in Inflammatory Diseases

Abstract: The inflammation biomarker Interleukin 6 (IL-6) exhibits a concentration of less than 7 pg/mL in healthy serum but increases 10–100-fold when inflammation occurs. Increased serum IL-6 has been reported in chronic diseases such as rheumatoid arthritis (RA), as well as in life-threatening acute illnesses such as sepsis and cytokine release syndrome (CRS). This work seeks to meet the demand for rapid detection of serum IL-6 both for rapid monitoring of chronic diseases and for triaging patients with acute illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The VFA addresses these issues by utilizing downward flow. Gravity assists in the capillary action of fluids, which helps yield faster results when compared to those obtained under lateral flow [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The VFA addresses these issues by utilizing downward flow. Gravity assists in the capillary action of fluids, which helps yield faster results when compared to those obtained under lateral flow [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Among cytokines released during CRS and other inflammatory states, IL-6 is the best known potent suppressor of CYP enzyme activity. 2,9 For example, in vitro studies have demonstrated that IL-6 incubated at physiological concentrations led to decreased expression or activity of CYP1A2, CYP2C9, CYP2C19, CYP3A4, and CYP3A5 in human hepatocytes. 3,10 Importantly, this change in CYP activity has been confirmed clinically in patients with RA, who present IL-6 systemic concentrations ~50 pg/mL, and with higher exposure in CYP substrates compared with healthy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Immunologically active proteins including interferons (IFNs), interleukins (ILs), and other cytokines are produced in response to infection or inflammation, and their systemic levels are elevated in chronic and acute inflammatory conditions, such as rheumatoid arthritis (RA) or cytokine release syndrome (CRS) 1,2 . Cytokines have been shown to alter the activity of cytochrome P450 (CYP) enzymes by affecting their stability or transcription factor activity for CYP enzyme expression, including PXR and CAR 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal physiological conditions, the levels of IL-6 in tissues and plasma are typically low. However, IL-6 expression increases rapidly and substantially when stimulated by pathogenic microorganisms such as bacteria, fungi, and viruses [6]. Numerous studies have shown that overproduction of IL-6 triggers a cytokine storm that leads to excessive inflammation in the body [7].…”
Section: Introductionmentioning
confidence: 99%